Long-term impacts of complete revascularization on clinical outcomes in patients with coronary chronic total occlusion - Tae Oh Kim; SeHee Kim; Min-Ju Kim; Do-Yoon Kang; Pil Hyung Lee; Soo-Jin Kang; Cheol Whan Lee; Young-Hak Kim; Jong-Young Lee; Seung-Whan Lee (Heliyon, 2024)
The impact of complete revascularization (CR), achieved through the recanalization of coronary chronic total occlusions (CTOs), on long-term patient outcomes remains uncertain.To evaluate this in patients who achieved CR after CTO-PCI with those who did not due to deferred CTO-PCI, the Asan Medical Center Registry was reviewed to identify coronary artery disease (CAD) patients with CTOs treated between January 2003 and December 2018. Patients were included with single-vessel disease with CTO and with multivessel disease who had undergone revascularization for non-CTO lesions. These subjects were divided into those who achieved CR with CTO-PCI and those who did not due to deferred CTO-PCI. Their outcomes were compared following 1:1 propensity score matching. Of the 2746 enrolled CAD patients with CTOs, 1837 achieved CR with CTO-PCI and 909 did not. Propensity score matching yielded 653 patient pairs. The CR-achieving group had a significantly lower 10-year risk of the primary composite outcome of death, myocardial infarction, stroke, or repeat revascularization (hazard ratio [HR]: 0.57; 95 % confidence interval [CI]: 0.46–0.72; P < 0.001), as well as significantly lower risks of death (HR: 0.66; 95 % CI: 0.51–0.87; P = 0.003) and repeat revascularization (HR: 0.67; 95 % CI: 0.48–0.95; P = 0.023). CR was beneficial in all subgroups, including patients with major cardiovascular risk factors such as older age, hypertension, diabetes, and advanced CAD. Compared with incomplete revascularization, CR may significantly reduce the 10-year incidence of major adverse cardiac events in patients with CTO.